Analisis Teknik Penerjemahan Lagu ‘Kun Anta’ oleh Humood Al Khuder Versi Bahasa Indonesia Berdasarkan Teori Molina dan Albir - aliffia shinta ghofrainy putri (Program Studi Pendidikan Bahasa Arab, 2025)
This study aims to identify and analyze the translation techniques used in the Indonesian version of the song lyrics “Kun Anta.” Using a qualitative approach and Molina and Albir’s theory, the research discusses eight main translation techniques found: adaptation, modulation, transposition, literal translation, reduction, amplification, borrowing, and linguistic substitution. The analysis reveals that adaptation and modulation are the most dominant techniques, reflecting the translator’s effort to adjust meaning and language style to fit the cultural context and target audience. This study emphasizes the importance of selecting appropriate translation techniques to maintain accuracy while preserving the beauty and musicality of the song lyrics.